Exploring the impact of financial development on renewable energy consumption within the renewable energy-environmental Kuznets curve framework in Sub-Saharan Africa - Prempeh, Kwadwo Boateng; Kyeremeh, Christian; Danso, Felix Kwabena; Yeboah, Samuel Asuamah (International Journal of Renewable Energy Development, 2024)
Renewable energy usage is deemed a feasible panacea to environmental degradation and energy poverty. In pursuit of carbon neutrality, nations are obligated to formulate strategies that bolster renewable energy initiatives following the Sustainable Development Goals of the United Nations. Given this, this article scrutinises the impact of financial development on the advancement of renewable energy consumption within the renewable energy- environmental Kuznets curve (REKC) framework while controlling for foreign direct investment (FDI), trade openness, governance and urbanisation using a panel of 38 Sub-Saharan African (SSA) nations from 2002-2019. The empirical findings based on the panel corrected standard error (PCSE) and the Feasible Generalized Least Squares (FGLS) models validated the REKC hypothesis for renewable energy consumption in the SSA region. Financial development, economic growth, trade openness, governance, and urbanisation have a substantial and detrimental impact on renewable energy consumption, whereas FDI has a neutral effect. The Dumitrescu-Hurlin causality tests demonstrate a bidirectional (feedback) causality between renewable energy consumption and all its determinants except for trade openness, where a unidirectional causality from renewable energy consumption to trade openness was established. Given these insights, our paper adds to empirical literature and provides incisive suggestions for policy formulation.